Cellulose conversion under heterogeneous catalysis - Dhepe, Paresh Laxmikant; Fukuoka, Atsushi (ChemSusChem, 2008)
In view of current problems such as global warming, high oil prices, food crisis, stricter environmental laws, and other geopolitical scenarios surrounding the use of fossil feedstocks and edible resources, the efficient conversion of cellulose, a non-food biomass, into energy, fuels, and chemicals has received much attention. The application of heterogeneous catalysis could allow researchers to develop environmentally benign processes that lead to selective formation of value-added products from cellulose under relatively mild conditions. This Minireview gives insight into the importance of biomass utilization, the current status of cellulose conversion, and further transformation of the primary products obtained
Keywords: Biomass; cellulose; heterogeneous catalysis; supported catalysts